Factors influencing the uptake of contraception services by Vatsonga adolescents in rural communities of Vhembe District in Limpopo Province, South Africa - Rachel T. Lebese; Sonto M. Maputle; Dorah U. Ramathuba; Lunic B. Khoza (AOSIS, 2013)
The aim of the study was to determine the factors that influence the uptake of contraception services by adolescents in the Vhembe district of Limpopo Province, South Africa. A qualitative research method which is explorative, descriptive and contextual in nature was used to investigate the phenomenon from the adolescents' perspective. The target population comprised of adolescents residing in one of the six villages of Vhembe District. Data was collected through six focus group discussions until data saturation was achieved. Data was analysed using an open coding method. The findings revealed that adolescents are aware of the availability of contraceptive services. However, they lack a comprehensive knowledge about contraception and contraceptives, which led to negative attitudes towards using the services. Cultural health beliefs and attitudes were also identified as a barrier to the uptake and use of contraceptives. Recommendations were made on interventions to increase the uptake of contraception services amongst adolescents.